Islamic Philosophy and Theology - Watt, William Montgomery (The New Edinburgh Islamic Surveys : NEIS, 2022)
This is the standard general account in English of Islamic philosophy and theology. It takes the reader from the religio-political sects of the Kharijites and the Shiites through to the assimilation of Greek thought in the medieval period, and onto the early modern period. Watt concludes with an analysis of Western influences on modern Islamic theology